2017
DOI: 10.1186/s12862-017-1098-5
|View full text |Cite
|
Sign up to set email alerts
|

Rates of morphological evolution, asymmetry and morphological integration of shell shape in scallops

Abstract: BackgroundRates of morphological evolution vary across different taxonomic groups, and this has been proposed as one of the main drivers for the great diversity of organisms on Earth. Of the extrinsic factors pertaining to this variation, ecological hypotheses feature prominently in observed differences in phenotypic evolutionary rates across lineages. But complex organisms are inherently modular, comprising distinct body parts that can be differentially affected by external selective pressures. Thus, the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 84 publications
(98 reference statements)
0
35
0
Order By: Relevance
“…In contrast, other studies identify clades with high rates of speciation and morphological evolution that are characterized by high levels of integration (Hu et al 2016;Sherratt et al 2017), possibly as a result of selection occurring along a single trajectory that may represent a line of least evolutionary resistance (Schluter 1996;Marroig and Cheverud 2005;Felice et al 2018). For example, Hu et al (2016) found high rates of speciation and morphological evolution coupled with high integration and neutral levels of disparity in icefish crania.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
“…In contrast, other studies identify clades with high rates of speciation and morphological evolution that are characterized by high levels of integration (Hu et al 2016;Sherratt et al 2017), possibly as a result of selection occurring along a single trajectory that may represent a line of least evolutionary resistance (Schluter 1996;Marroig and Cheverud 2005;Felice et al 2018). For example, Hu et al (2016) found high rates of speciation and morphological evolution coupled with high integration and neutral levels of disparity in icefish crania.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
“…; Sherratt et al. ). Although claw loss has never been observed in anoles, dramatic claw reduction and even complete loss are observed in toepad‐bearing geckos (Russell and Bauer ; Khannoon et al.…”
Section: Discussionmentioning
confidence: 98%
“…Loss of function is common in traits that do not provide fitness benefits in particular populations or species (Fong et al 1995) and may explain the rapid evolutionary rate of claws, but not of toepads, in twig anoles (Tables 2 and 3; Fig. S3) through release from biomechanical constraint (Adams et al 2017a;Sherratt et al 2017). Although claw loss has never been observed in anoles, dramatic claw reduction and even complete loss are observed in toepad-bearing geckos (Russell and Bauer 2008; Khannoon et al 2015).…”
Section: Anoles?mentioning
confidence: 99%
See 2 more Smart Citations